(untitled) - Nagaraj Murthy; Rajesh Raman (Asian Journal of Medical Radiological Research, 2018)
Background: The aim of the study is to assess the correlation between non-specific mesenteric lymphadenitis in children with cervical lymphadenopathy. Subjects and Methods: Total of 172 cases with Ultrasound features of non-specific mesenteric lymphadenitis reported in Department of Radiology, JSS medical college hospital, Mysore during the period of October 2016 & July 2018 were included in the study and correlated with Ultrasound of the neck. The clinical profile and attributed causes of these cases were correlated and evaluated. Results: Out of 172 cases, 60.5% of cases presented with pain abdomen being the most common symptom. Upper respiratory symptoms were noted in 37.2% of cases, diarrhea in 6.4% cases, urinary tract symptoms in 3.5% and fever in 18.6% of cases. Cervical adenopathy was noted in 72 cases (41.9%) of total cases out of which 55 cases had signs of upper respiratory tract infection. Conclusion: Ultrasound diagnosis of non specific mesenteric lymphadenitis is important to differentiate it from other causes of pain abdomen. Upper respiratory tract infection is one of the most common causes of non specific mesenteric adenitis and is associated with cervical adenopathy.